ANALISIS TINGKAT EFEKTIVITAS WORK-LIFE BALANCE PADA PEKERJA INDUSTRI MANUFAKTUR DI KOTA BATAM - Afrinanda Afrinanda; Nanda Harry Mardika; rina rina; Andri Hanico Andri Hanico (Yayasan Tri Edukasi Ilmiah, 2026)
Work-life balance has become an important issue in the manufacturing industry due to increasing job demands, shift work systems, and production targets that may affect employees' personal lives. This study aimed to analyze the effectiveness of work-life balance among manufacturing workers in Batam City. The research employed a quantitative descriptive approach using a questionnaire distributed to 150 manufacturing employees selected through incidental sampling. Data were analyzed using the Respondent Achievement Level (TCR) method. The results showed that the overall work-life balance score reached 72.01%, indicating an effective category. Among the three dimensions measured, Involvement Balance achieved the highest score, reflecting employees’ ability to maintain engagement in both work and personal life. In contrast, Time Balance recorded the lowest score, particularly regarding the allocation of time between work and personal activities. The findings suggest that although work-life balance among manufacturing workers in Batam is generally effective, improvements in work scheduling, overtime management, and employee welfare programs are needed to enhance time balance and overall employee well-being.